The development of an advanced practice nursing (Child Health Nurse Practitioner) curriculum framework for Sub-Saharan Africa: a multi-method study - Christmals, Christmal Dela (My University, 2018)
Background: Nurses are the majority of readily available healthcare professionals in Sub- Saharan Africa (SSA), therefore, improving access to Advanced Practice Nursing (APN) programmes in order to improve healthcare within SSA where preventive services are much needed is essential. Sub-Saharan Africa is unique in terms of its challenges, opportunities and health need hence an APN (Child Health) curriculum must be designed and continually reviewed to meet the needs of the continent. Professional education has not kept pace with SSA’s special healthcare challenges, largely because of fragmented, outdated, and static curricula that produce ill-equipped graduates. Aim: The aim of this study is to develop a curriculum development framework to guide governments and Nursing Education Institutions in the development of relevant Advanced Practice Nursing (Child Health Nurse Practitioner) curriculum that responds to the child healthcare needs of Sub-Saharan Africa Methodology: A sequential multi-method research design was employed in this study. The study began with a scoping review, followed by a Delphi, then concept development, and the development, confirmation and evaluation of the curriculum framework. Findings: Children are the majority of Sub-Saharan Africa. Between 70-90% of the Sub- Saharan African population is rural and lack access to quality and cost-effective healthcare services as most healthcare facilities are located in the cities and small towns. The implementation of Advanced Practice Nursing programmes is essential in increasing access to quality healthcare services for the majority and marginalized rural population of Sub-Saharan Africa. The introduction of Advanced Practice Nursing programmes is challenged by the opposition from the medical profession, the existence of lower cadre medical professionals, meagre resource allocation, lack of scope of practice, lack of context-specific benchmark programmes and lack of political will. The need to increase access to quality healthcare to the rural population, the push for Primary Health Care, the dominance of nursing professionals in the healthcare system of Sub-Saharan Africa, the existence of resource sharing opportunities were facilitating factors. A concept-based Child Health Nurse Practitioner curriculum framework for Sub-Saharan Africa was developed. Conclusion: The Child Health Nursing Practitioner curriculum framework is comprehensive, context-specific, has the potential to respond to the special child healthcare needs of Sub-Saharan Africa and is adaptable for other Advanced Practice Nursing speciality programmes in Sub-Saharan Africa.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Doctor of Philosophy in Nursing. Johannesburg, 2018.
Keywords: Nursing; Primary health care; Nurse practitioners